2017
DOI: 10.1038/s41598-017-02539-w
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive mass spectrometry platform identifies metabolic changes of life history traits in C. elegans

Abstract: Abnormal nutrient metabolism is a hallmark of aging, and the underlying genetic and nutritional framework is rapidly being uncovered, particularly using C. elegans as a model. However, the direct metabolic consequences of perturbations in life history of C. elegans remain to be clarified. Based on recent advances in the metabolomics field, we optimized and validated a sensitive mass spectrometry (MS) platform for identification of major metabolite classes in worms and applied it to study age and diet related c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(115 citation statements)
references
References 38 publications
5
108
2
Order By: Relevance
“…Interestingly, a recent study in C. elegans that examined the effect of age on metabolite profiles reported that FA levels in wild-type and aak-2 null mutants are very similar at day 1. However, there is an increase in wild-type FA levels at day 7 that is blunted in aak-2 mutants (Gao et al, 2017), which led us to hypothesize that activating AMPK might increase lifespan via a shift to FAO as animals age. In support of a causal role for FAO, treatment with PHX has no effect on wild-type animals but reduces lifespan extension by 50% in CA-AAK-2 animals (Figures 7C and 7D; Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a recent study in C. elegans that examined the effect of age on metabolite profiles reported that FA levels in wild-type and aak-2 null mutants are very similar at day 1. However, there is an increase in wild-type FA levels at day 7 that is blunted in aak-2 mutants (Gao et al, 2017), which led us to hypothesize that activating AMPK might increase lifespan via a shift to FAO as animals age. In support of a causal role for FAO, treatment with PHX has no effect on wild-type animals but reduces lifespan extension by 50% in CA-AAK-2 animals (Figures 7C and 7D; Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…We reported that the concentrations of most amino acids peak at the later larval stage or early adult phase and then began declining at different adult stages, reaching low levels by the latest stages of the animals' life (21). One stark exception was glycine, which continued to accumulate in aged worms (21).…”
Section: Genes Coding For Glycine Degradation Enzymes Decrease With Amentioning
confidence: 98%
“…We previously measured amino acid levels throughout the life of C. elegans, including four larval phases (L1-L4) and ten days of adulthood from young worms to aged ones (days 1-10) (21). We reported that the concentrations of most amino acids peak at the later larval stage or early adult phase and then began declining at different adult stages, reaching low levels by the latest stages of the animals' life (21). One stark exception was glycine, which continued to accumulate in aged worms (21).…”
Section: Genes Coding For Glycine Degradation Enzymes Decrease With Amentioning
confidence: 99%
See 1 more Smart Citation
“…The longevity of C. elegans was measured using a previously described method by Smolentsevae et al [32]. In the experiment, 50 μL of the target bacterial strain cultured in TS and MRS broth at 25°C for 24 h was spread on a 35 mm diameter NGM agar plate and incubated overnight at 37°C.…”
Section: Nitric Oxide Production In Lactobacillusmentioning
confidence: 99%